2d Animated Design of “Menembus Debus Dan Melampauinya” as Media Information and Education About Debus Ciburial - Aisya Fathinannisa Junaedy; Fiandra, Yosa; Muhammad Yudhi Rezaldi (KalaTanda, 2025)
Lack of knowledge of young people in the city of Bandung about Debus martial arts in Ciburial village due to the era ofmodernization. The design of 2D Animation as a medium for cultural preservation and education about Debus martial arts inCiburial Village aims to introduce, inform, and educate the public, especially young people in Bandung who do not know theDebus martial arts in Ciburial Village. this research uses qualitative and quantitative methods, where researchers conductobservations and interviews in Ciburial Village. the quantitative method that researchers use is distributing questionnairesto young people who live in Bandung. to strengthen data about their ignorance about Debus martial arts and whether theanimation can attract teenagers’ interest in Debus martial arts. many young people in Bandung City know what Debusmartial arts is, but they don’t know the existence of Debus in Ciburial Village. after watching the animation ”MENEMBUSDEBUS AND MELAMPAUINYA”, the message in the animation about Debus Ciburial was conveyed well, many youngpeople in Bandung City claimed to be interested in knowing more about this culture. Based on the data and research resultsin the design of this 2D animation, it can be concluded that there are still many young people in Bandung who do not knowhow the Debus martial art in Ciburial Village. therefore the author designed a 2D animation entitled ”MENEMBUS DEBUSAND MELAMPAUINYA” as a media of information and education about the Debus martial art in Ciburial Village.